Development of a portable DNA extraction and cross-priming amplification (CPA) tool for rapid in-situ visual diagnosis of plant diseases - Li, J.; Du, J.; Li, S.; Dong, J.; Ying, J.; Gu, Y.; Lu, J.; Zeng, X.; Kear, P.; Dou, D.; Wang, X. (Springer, 2023)
Plant pathogens cause severe losses to crop yields and economic returns in agriculture. Despite plant tissue DNA extraction of typically constituting a preliminary step in nucleic acid-based molecular diagnostics, such lab-based methods can be time-consuming and arduous to complete many samples. To mitigate these challenges, we developed an inexpensive portable DNA extraction technique that is lightweight and suitable for deployment in sampling locations, such as fields. It includes a DNA extraction device fabricated with a Steel Microneedle Array (SMA) and a simple high-efficiency DNA extraction buffer. As a result, DNA extraction times can be reduced to within ~ 1 min, and the eluted DNA is demonstrated to be suitable for subsequent molecular biological analyses without requiring additional purification. Cross-priming amplification (CPA) technology was first established to detect Phytophthora infestans, which achieves sensitivity attainment of 10–7 ng/µL. The detection result can be conveniently estimated with naked-eye visual inspection using fluorescent dsDNA binding dye. CPA was demonstrated to be more feasible than PCR-based approaches and performed well in species-specific and practicability tests. This study elucidates a novel integrated pathogen detection technique coupled with SMA-Device extraction and a modified visual CPA assay to establish and verify various field-based samples infected with multiple pathogens. Altogether, the total sample-to-answer time for pathogen detection was reduced to ~ 1.5 h, making field-based analysis affordable and achievable for farmers or extension workers inside and outside the laboratory.